Pengurangan Lead time Picking dan Put away dengan Perancangan Tata Letak Material pada BLP PT. Schneider Electric - Leonardus Glenn Gunawan; Herri Christian Palit (Jurnal Titra, 2020)
The Batam Locistics Platform (BLP) plant is a plant owned by PT. X. PT. X itself is a company engaged in the assembly of electronic equipment which is one branch of a company from France. The BLP plant is a warehouse that has the role to handle all logistics activities of the production plant at PT. X. The BLP plant has a target to increase productivity by reducing lead time on picking and put away. The put away section has the task of laying down the material that has been received. The picking department has the duty to take material that is ordered by the production plant. The problem that causes high lead time on the picking and put away parts is that the material is spread over too wide limits. The opportunity for improvement that results from observations is to place a booking in accordance with the Supply Chain Management forecast for each material in the BLP plant. Improvements made can reduce the lead time of the picking part by 45% and the lead time of the put away part by 15.47%